Tuberculosis of greater trochanter presenting as avulsion fracture of greater trochanter-A case report - Dulani, Rajesh (Asian Pacific Tropical Medicine Press, 2013)
Isolated tuberculosis of greater trochanteris unusual and clinical presentation is often vague. Isolated fracture of greater trochanter is also rare. We are reporting a case of tuberculosis of greater trochanter in adult female with radiological presentation in form of avulsion fracture of greater trochanter which has not be reported in literature till now to our knowledge.